AKTIVITAS DAN MOTIVASI BELAJAR DI RUMAH DALAM HUBUNGANNYA DENGAN HASIL BELAJAR SISWA KELAS IV - Ririn Murdianti; Budiman Tampubolon; Tahmid Sabri (Universitas Tanjungpura, 2020)
Abstract This study aims to find out the relationship between learning activities and learning motivation together with the learning outcomes of grade 4 students of Public Elementary School 38 Sengawang Hilir. The research method used is descriptive with the form of correlation study research. The population in this study was students of Public Elementary School 38 Sengawang Hilir. A sample of 25 people was determined by nonprobabilty sampling techniques. The data source of this research is grade 4 students of Public Elementary School 38 Sengawang Hilir and documents the average rapot value. The data is a questionnaire score of learning activities, learning motivation and average rapot value. The results showed student learning activities by 76%, student learning motivation by 80.28%, and learning outcomes by 82.76%. The correlation between learning activity and learning outcomes was 0.514. The correlation between learning motivation and learning outcomes was 0.549. Correlation of learning activity and learning motivation was 0.627. The correlation between learning activities and learning motivation together to learning outcomes was 0.590. So it can be concluded that there is a relationship between learning activities and learning motivation together with learning outcomes. Keywords : Learning Activity, Learning Motivation, and Learning Outcomes.